Compass and Dead Reckoning: The Dynamic Implications of ISCT - Donaldson, Thomas (Journal of business ethics, 2009)
The dynamic relationship between hypernorms and microsocial contracts can explain novel, evolutionary changes in economic life. The conceptual machinery of Integrative Social Contracts Theory (ISCT) can be expanded in order to understand dynamic moments in the evolution in economic life such as the economic crisis of 2008–2009. When a transition in the ethical interpretation of economic events occurs over time, it can be understood as a transition from the opaqueness of hypernorms to the relative clarity of microsocial contracts. This phenomenon deserves more study than it has received, and entails, at a minimum, the application of an enhanced, more dynamic interpretation of ISCT.